2018
DOI: 10.1017/s0022109018001175
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Trading Competition

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Previous work examining HFT's impact on liquidity deliver mixed results (see for example Brogaard, 2010;Hasbrouck and Saar, 2013;Jain et al, 2016;Li et al, 2018;Baldauf and Mollner, 2020;Ammar et al, 2020 for the positive effects; and Egginton et al, 2016;Kirilenko et al, 2017;Breckenfelder, 2019 for the negative effects). It is widely suggested that HFT improves market quality by providing liquidity (e.g., Malinova et al, 2013;Menkveld, 2013;Brogaard and Garriott, 2019;Jarnecic and Snape, 2014;and Aït-Sahalia and Saglam, 2013). On the contrary, many studies show large amounts of correlated liquidity withdrawal HFTs are engaged in (e.g., Van Kervel, 2015;Cespa and Foucault, 2014;Anand and Venkataraman, 2016;Malceniece et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work examining HFT's impact on liquidity deliver mixed results (see for example Brogaard, 2010;Hasbrouck and Saar, 2013;Jain et al, 2016;Li et al, 2018;Baldauf and Mollner, 2020;Ammar et al, 2020 for the positive effects; and Egginton et al, 2016;Kirilenko et al, 2017;Breckenfelder, 2019 for the negative effects). It is widely suggested that HFT improves market quality by providing liquidity (e.g., Malinova et al, 2013;Menkveld, 2013;Brogaard and Garriott, 2019;Jarnecic and Snape, 2014;and Aït-Sahalia and Saglam, 2013). On the contrary, many studies show large amounts of correlated liquidity withdrawal HFTs are engaged in (e.g., Van Kervel, 2015;Cespa and Foucault, 2014;Anand and Venkataraman, 2016;Malceniece et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Breckenfelder (2019) analyzes a channel through which HFTs may reduce market liquidity, namely the competition, and detects that market liquidity deteriorates through higher competition among HFTs. Other studies, such as Bernales ( 2019), and Brogaard and Garriott (2019), focus also on HFT competition in the examination of HFT's role in liquidity. Brogaard and Garriott (2019) examine a sample from Alpha, a recently introduced Canadian stock market.…”
Section: General Impacts Of Hft On Liquiditymentioning
confidence: 99%
See 2 more Smart Citations
“…Developments in trading technologies fostered the use of an automated and very fast trading infrastructure. The increase in algorithmic trading over recent years, considered beneficial by many in terms of increasing market efficiency due to increased liquidity (Hendershot et al 2011), facilitation of larger trades (Hasbrouck and Saar 2013), improved pricing discovery (Brogaard and Garriott 2019), lower trading costs (Chlistalla 2011) and narrower bid-ask spreads (Hagströmer and Norden 2013) also created new risks. The regulation of high-frequency algorithmic trading by MiFID II has an aim of promoting financial stability and ensuring orderly markets, interrupting period of excessive volatility in order to give investors the possibility to reassess their positions.…”
Section: Introductionmentioning
confidence: 99%